Medical blogs: classification and necessity for modern doctor - Alutina, K. D. (Запорізький державний медико-фармацевтичний університет, 2023)
Aim of the research. To analyze the structure of medical blogs, their classification and actuality in nowadays medical practice. To form an understanding of the responsibility for the sharing of information on the Internet among medical students is extremely important for their formation as future doctors.
Keywords: тези доповідей